2017
DOI: 10.3390/cryst7050145
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Structural Distortions of Mixed-Metal Oxide Photocatalysts Constructed with α-U3O8 Types of Layers

Abstract: Abstract:A series of mixed-metal oxide structures based on the stacking of α-U 3 O 8 type pentagonal bipyramid layers have been investigated for symmetry lowering distortions and photocatalytic activity. The family of structures contains the general composition A m+ ((n+1)/m) B (3n+1) O (8n+3) (e.g., A = Ag, Bi, Ca, Cu, Ce, Dy, Eu, Gd K, La, Nd, Pb, Pr, Sr, Y; B = Nb, Ta; m = 1-3; n = 1, 1.5, 2), and the edge-shared BO 7 pentagonal pyramid single, double, and/or triple layers are differentiated by the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 129 publications
(226 reference statements)
0
5
0
Order By: Relevance
“…The structure is comprised of layers of linearly-coordinated Cu(I) and octahedrally-coordinated Ta(V) cations that alternate with double layers of edge-and vertex-shared TaO 7 pentagonal bipyramids. The layers of pentagonal bipyramids, i.e., the TaO 7 in Figure 1b, are similar to those previously described in the structure of α-U 3 O 8 [24]. To probe the bulk and surface-level thermal stability of Cu3Ta7O19, the crystalli were heated in air at temperatures spanning the range of 350 °C to >550 °C.…”
Section: Bulk Phase Analysis and Thermal Stabilitymentioning
confidence: 63%
“…The structure is comprised of layers of linearly-coordinated Cu(I) and octahedrally-coordinated Ta(V) cations that alternate with double layers of edge-and vertex-shared TaO 7 pentagonal bipyramids. The layers of pentagonal bipyramids, i.e., the TaO 7 in Figure 1b, are similar to those previously described in the structure of α-U 3 O 8 [24]. To probe the bulk and surface-level thermal stability of Cu3Ta7O19, the crystalli were heated in air at temperatures spanning the range of 350 °C to >550 °C.…”
Section: Bulk Phase Analysis and Thermal Stabilitymentioning
confidence: 63%
“…In the case of the binary oxide compound Ca 12 Al 14 O 33 , firing in a reducing atmosphere results in the removal of occluded oxygen atoms, replacing them with other atoms, molecules, or electrons, where the latter can alter the conduction from highly resistive to near-metallic. King et al [10] showed that mixed-metal oxide compounds, with the general formula A m+ ((n+1)/m) B (3n+1) O (8n+3) , phase transitions that occur from varying the temperature, the composition, or the chemical reactions, can result in structural and electronic distortions that impact the efficiency of the photocatalysis. Two of the papers reported the crystal structures of new compounds along with complementary property measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In photoelectrochemical water splitting, the electricity used to produce the hydrogen is supplied by a renewable energy source (i.e., a photovoltaic system). In the paper presented by King et al [10], the authors review crystal structures having photocatalytical properties. This paper focuses on a series of mixed-metal oxide structures, based on the stacking of α-U 3 O 8 type pentagonal bipyramid layers, with the general formula A m+ ((n+1)/m) B (3n+1) O (8n+3) , where the A cation can be Ag, Bi, Ca, Cu, Ce, Dy, Eu, Gd K, La, Nd, Pb, Pr, Sr, or Y, the B cation is either Nb or Ta, and m = 1-3 and n = 1, 1.5, 2.…”
Section: Photocatalysis Materials Constructed Using α-U 3 O 8 Types Omentioning
confidence: 99%
“…However, though the structural symmetry of orthorhombic KNbO 3 is lower than that of tetragonal KNbO 3 , it presents a better performance, probably due to better morphology, that is, the exposed facets and the associated electronic structure. In contrast, King et al have found that structure distortions lowering the symmetry have an influence on the photocatalytic performance, for example, for PbTa 4 O 11 with an out-of-plane distortion of the d 0 transition metal cation, an internal electric dipole can facilitate the separation of charge carriers (electron/hole), hindering the recombination and back-reaction [32]. Finally, Huang et al have reviewed synthesis methods for symmetry-breaking in multicomponent NPs, concluding that NPs with broken symmetry could be beneficial for various photocatalytic and electrocatalytic reactions resulting from: (i) arrangement of one-direction of charge migration, (ii) spatial separation of domains (prevention of reverse reactions), and (iii) synergism at the interface of different domains [33].…”
Section: Introductionmentioning
confidence: 95%